Down-Regulation of Toll-Like Receptor 5 (TLR5) Increased VEGFR Expression in Triple Negative Breast Cancer (TNBC) Based on Radionuclide Imaging - Jiang, Wen; Han, Yeming; Liang, Ting; Zhang, Chao; Gao, Feng; Hou, Guihua (Frontiers in Oncology, 2021)
In this study, GFP-tagged TNBC 4T1 cells with down-regulated TLR5 expression (TLR5− 4T1) and normal TLR5 expression (TLR5+ 4T1) were constructed, respectively. RT-PCR and western-blot studies showed down-regulation of TLR5 obviously increased the expression of VEGFR in 4T1 cells. Highly stable radio-probes 125I-anti-TLR5 mAb/125I-VEGF/125I-IgG were obtained with labeling rates over 85% and radiochemical purities above 90%. Among these three probes, 125I‑anti‑TLR5 mAb and 125I-VEGF were used for specifically imaging TNBC, while 125I-IgG was used for comparison. Whole-body phosphorus autoradiography showed clear imaging at 48 h after injection of 125I-anti-TLR5 mAb and 125I-VEGF also provided clear imaging at 24 h. Biodistribution study demonstrated a higher tumor uptake of 125I-anti-TLR5 mAb in TLR5+ group compared with that in TLR5- group (P < 0.05), while tumor uptake of 125I-VEGF in TLR5+ group was lower than that in TLR5- group (P < 0.05). Immunohistochemical staining suggested that the expression of TLR5 was lower, while the expression of VEGFR, CD31 and MVD (microvessel density) was higher in TLR5- tumor-bearing mice.